Answer:
The proof is given below.
Step-by-step explanation:
Given:
[tex]f'(x)\leq 2,\ f(0)=4, \ x>0[/tex]
Using Mean Value Theorem,
[tex]f'(c)=\frac{f(b)-f(a)}{b-a}[/tex]
Here, [tex]a=0,\ b=x[/tex]
Therefore, [tex]f'(c)=\frac{f(x)-f(0)}{x-0}=\frac{f(x)-4}{x}[/tex]
Now, as per question the derivative of [tex]f(x)[/tex] is less than or equal to 2.
Therefore, [tex]f'(c)\leq 2[/tex]. Plug in the value of [tex]f'(c)[/tex]. This gives,
[tex]\frac{f(x)-4}{x}\leq 2\\f(x)-4\leq 2x ...............(\textrm{Cross product})\\f(x)\leq 2x+4 ..............(\textrm{Adding 4 both sides})[/tex]
Therefore, we get, [tex]f(x)\leq 2x+4[/tex] and hence it is proved using mean value theorem.